Leveraging Customer Experience, Brand Image and Store Atmosphere for Millennials Loyalty: An Empirical Analysis of Mediation - Nanggong, Ardiwansyah; Mohammad, Ali; Sabila, Alfa (Universitas Negeri Semarang, 2022)
The increasing population and unique consumer behavior of millennials is a challenge for companies in offering products and retention this segment. The current study aims to investigate the millennial loyalty behavior and its brand-atmosphere mechanism in formatting customer experience. The study on visitors to Warunk Upnormal in Gorontalo was 170 samples of respondents with purposive sampling through questionnaires. Regression data analysis used SPSS Process Macro 3.4 program and mediation check conducted with Sobel test. The research findings indicate that brand image and store atmosphere have a direct and significant effect on customer experience but not significantly on consumer loyalty. Furthermore, the customer experience dimensions have a different impact in mediating the relationship between brand image and store atmosphere in increasing consumer loyalty. This study reinforce the role of the experiential economy in exploring millennial consumer behavior.